Neighborhood effects and housing vouchers - Morris A. Davis; Jesse Gregory; Daniel A. Hartley; Kegon T.K. Tan (Quantitative Economics, 2021)
Researchers and policy makers have explored the possibility of restricting the use of housing vouchers to neighborhoods that may positively affect the outcomes of children. Using the framework of a dynamic model of optimal location choice, we estimate preferences over neighborhoods of likely recipients of housing vouchers in Los Angeles. We combine simulations of the model with estimates of how locations affect adult earnings of children to understand how a voucher policy that restricts neighborhoods in which voucher-recipients may live affects both the location decisions of households and the adult earnings of children. We show the model can nearly replicate the impact of the Moving to Opportunity experiment on the adult wages of children. Simulations suggest a policy that restricts housing vouchers to the top 20% of neighborhoods maximizes expected aggregate adult earnings of children of households offered these vouchers.
Keywords: I24; I31; I38; J13; R23; R38; 330; Neighborhood choice; housing vouchers